Internet das coisas aplicada à indústria: dispositivo para interoperabilidade de redes industriais - Keller, Armando Leopoldo (Universidade do Vale do Rio dos Sinos, 2017)
The objective of this work is to develop a more comprehensive study on the concept of Internet of Things (IoT) and its main protocols, specifically exploring the concept of IoT applied in automation systems. A bibliographic review explores the diverse protocols developed for IoT applications, characterizing them as transmission rate, efficiency, safety and confiability. A survey of the current scenario about the application of IoT protocols in automation systems is presented, always having the system confiability in mind. The heterogenity of the existent networks makes the use of this protocols a harder task. The proposal of this work is develop a device that acts as middleware for interlink distributed automation networks, in this case the Modbus RTU networks, in a transparent way using the internet of things procol MQTT (Message Queuing Telemetry Transport). This device is tested with equipments in a real scenario trough a case study, where two Modbus RTU networks of a geographically distributed solar photovoltaic power plant, is interlinked, allowing the criation of a VPP (Virtual Power Plant). This makes possible to manage the distributed power generator systems as a single generator unit, improving the electric energy dispatch. To prove the efficiency and confiability of the system, tests were made where the time between request and response was mensured, and based on his distribution the time of 2.5 seconds was determined to have a low message loss communication. Those tests validate the proposed system and the achievement of the goals of the present work.
Keywords: Internet das coisas; Máquina para máquina; Internet industrial das coisas; MQTT; Internet of things (IoT); Machine to machine (M2M); Industrial internet of things (IIoT); Modbus; ACCNPQ::Engenharias::Engenharia Elétrica